Idade e crescimento do robalo-flecha, Centropomus undecimalis (BLOCH, 1792) e robalo-peva, Centropomus parallelus (POEY, 1860) (OSTEICHTHYES: CENTROPOMIDAE), no Sudeste do Brasil - Carvalho, Maria Odete Ximenes (2006)
The common snook, Centropomus umdecimalis, and the fat snook, Centropomus parallelus, are two species that dwell on estuarine and costal marine environments along the North, Northeast and South Brazil, hence with great potential for mariculture. The estimation of age and growth parameters, the primary objective of this paper, should supply the necessary information to evaluate the cost/benefit ratio for the development of marine fish farms, especially as to feeding efficiency in promoting the enhancement of growth rates in comparison to that of wild populations. The databank was obtained by means of sampling of the landings made at the São Pedro fishmarket, in Niterói, Rio de Janeiro State, by the commercial fleet of liners which fish for pelagic resources off Cabo Frio’s coast (23oS) The collected material was comprised of 264 specimens, 130 of C. undecimalis and 134 of C. parallelus, in the period from June, 1999 through June, 2000. From a site below the pectoral fin scales were drawn for age and growth studies to be performed by means of the identification of age rings and measurement of growth bands. Total lengths of the sampled fish were in the range of 33.1 – 78.9 cm (C. undecimalis) and 29.5 – 57.3 cm (C. parallelus). The basic assumptions on the dependence of fish size on scale size, and the periodicity in age rings formation were investigated by regression equations and monthly variations in the scale’s marginal increment, respectively. The parameters of the growth equation, namely asymptotic length, growth coefficient and theoretical age at birth, and growth performance index as well were estimated. The natural mortality coefficient (M) was calculated in order to make up the M/K ratio. Statistical analyses were used in order to compare the growth rate between common snook and fat snook through Student’s t test, and to assess the significance of age changes between pairs of adjoining months through Kruskal-Wallis’ H test. The drawn results may be summarized as follows: (a) the assumption of a regression of scale length on fish length was met; (b) the “birth dates” of common snook and fat snook correspond with April-June and August-October monthly periods; (c) the age and growth parameters for common snook were: L = 101. 1 cm, W = 11.4 kg, K = 0.112, t0 = - 2.59 yr., tmax = 29.3 yr. and f’ = 3.058; (d) the age and growth parameters for fat snook were: L = 67.9, W = 3.6 kg, K = 0.187, t0 = - 2.48 yr., tmax = 18.6 yr. and f’ = 2.936; (e) the fat snook reaches a smaller size but grows quicker than the common snook; (f) the natural mortality coefficient was estimated at M = 0.259 (C. undecimalis) e M = 0.406 (C. parallelus), entailing respective values of M/K = 2.312 and M/K = 2.171, which classify those species into the fourth trophic level; (g) The growth performance indices indicate the adoption of a strategy consistent with that assumed by mean- and large-sized predatory species.